(untitled) (Bulletin of the International Association for Paleodontology, 2019)
A partial skeleton of an elderly man, suffered from cerebral palsy, is described. The person died in the collapse of the building destroyed by the fire in the stronghold of Tver, most likely during the siege of the city by the hordes of Batu Khan in 1238. Located at the basement of the structure, the body of a man was not exposed to fire, unlike the bodies of an elderly woman, a girl and a child who died in the same house. Unsuitable for the protection of the city these people died in the building where they were hiding